Aromatic (co)polycarbonates bearing pendant 2,3-dimethylmaleimido group based upon a new phthalimidine-containing "cardo" bisphenol - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
A new ``cardo'' bisphenol viz., 1-(2-(1,1-bis(4-hydroxyphenyl)-3-oxoisoindolin-2-yl)ethyl)-3,4-dimethyl- 1H-pyrrole-2,5-dione (PPH-MA) was synthesized in a two-step reaction sequence starting from phenolphthalein. PPH-MA was utilized as a step-growth monomer for the synthesis of a homo- and fourco-polycarbonates bearing pendant 2,3-dimethylmaleimido groups (PC-MAs) via solution polycondensation of PPH-MA or various mol % compositions of PPH-MA and bisphenol-A, respectively, with triphosgene.H-1 NMR spectroscopy confirmed the chemical structure and composition of PC-MAs. Inherent viscosity and number average molecular weight values of PC-MAs were in the range 0.45-0.64 dL g(-1) and 18,300 - 36,200 g mol(-1), respectively, indicating the formation of polymers of medium to reasonably high molecular weights. Tough, transparent and flexible films of PC-MAs could be cast from chloroform solution. X-ray diffraction studies indicated the amorphous nature of PC-MAs. The 10% weight loss temperature (T-10) values of PC-MAs were in the range 373-443 degrees C indicating their good thermal stability.
Keywords: (co)polycarbonates; 2; 3-dimethylmaleimido; phenolphthalein; phthalimidine ring; ``cardo'' bisphenol